2019
DOI: 10.1021/acs.jpca.9b00307
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Impulsive Vibrational Spectroscopy

Abstract: In the present work we applied a fully atomistic electron−nuclear real-time propagation protocol to compute the impulsive vibrational spectroscopy of the five DNA/RNA nucleobases in order to study the very first steps (subpicosecond) of their energy distribution after UV excitation. We observed that after the pump pulse absorption the system is prepared in a coherent superposition of the ground and the pumped electronic excited states in the equilibrium geometry of the ground state. Furthermore, for relatively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…Regarding this point, the implementation of the semiclassical Ehrenfest method for nuclear-electron dynamics in DFTB+ allow us to consider the nuclei motion within the TD-DFTB approach. This method has already been successfully used to study coherent breathing oscillations on metal nanoparticles, 45 transient absorption spectra in organic molecules, 46 impulsive vibrational spectroscopy on biological systems, 47 and photoinduced charge transfer in sensitized nanodiamonds. 22 In a experimental work of M.S.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding this point, the implementation of the semiclassical Ehrenfest method for nuclear-electron dynamics in DFTB+ allow us to consider the nuclei motion within the TD-DFTB approach. This method has already been successfully used to study coherent breathing oscillations on metal nanoparticles, 45 transient absorption spectra in organic molecules, 46 impulsive vibrational spectroscopy on biological systems, 47 and photoinduced charge transfer in sensitized nanodiamonds. 22 In a experimental work of M.S.…”
Section: Introductionmentioning
confidence: 99%
“…We have studied the good correlation between the IV spectrum and the PED in previous works. 21,88 What is different in this case, as shown in figure 7, is the drop in intensity in both the IV spectrum and the PED for the peaks centered in 448 and 1830 cm −1 . We have observed that these modes are the most coupled with the Soret transition, 21 in a partial agreement with experimental evidence.…”
Section: Ultra-fast Dynamics Of Zntpp On-and Off-resonancementioning
confidence: 62%
“…In previous works, 21,88 we have proposed interpreting the IV spectrum along with the potential energy distributed (PED) on ground-state normal modes after the pulse. The PED is obtained from the pump-only trajectory projecting the nuclear displacements onto normal modes coordinates as follows: 98…”
Section: Ultra-fast Dynamics Of Zntpp On-and Off-resonancementioning
confidence: 99%
“…Compared to other methods for computing non-adiabatic dynamics, the focus is shifted away from potential-energy surfaces (PES) towards a real-space representation based on the charge density. Further conclusions can be drawn from direct simulations of third-order spectroscopy, which is fairly straightforward with RT-TDDFT or related real-time methods [38][39][40][41][42].…”
mentioning
confidence: 99%